Environmental bargaining in Australia. (February 2019) - Markey, Raymond; McIvor, Joseph
An emerging body of research addresses the link between environmental issues, especially climate change, and employment relations. In this article, we examine the ways in which employment relations actors are addressing climate change, particularly focusing on collective bargaining. We begin by surveying the literature linking climate change and employment relations, especially analysing union strategies in this sphere, and develop a conceptual framework linking these threads. We then examine the incidence and content of collective enterprise bargaining over environmental issues in Australia for 2011–2016, applying and adaptingGoods' concepts of embedded institutional and voluntary multilateral approaches. The former inserts environmental commitments into formal collective agreements; the latter involves unions and workers more directly in developing emissions-reduction activities in the workplace. We address the potential links between these and the different actors (unions or management) that drive them. We find that environmental clauses in Australian agreements are rare, and that they are as likely to be driven by management as by unions. The institutional, organisational, and particularly the regulatory environment seem responsible. However, exceptions – notably in universities – provide exemplars for substantial, class-based union agency. We also find that collective bargaining may facilitate more ongoing, strategic initiatives of the voluntary multilateral type.